A CONTEXTUAL MEANING ON ADELE’S SONG SOMEONE LIKE YOU - Rasuh, Mishelia Cindy; Posumah, Jenie; Rombepajung, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
In semantics, “contextual meaning” refers to the meaning of a word, phrase, or sentence that is understood based on the context in which the word or sentence is used. Learning to understand contextual meaning in songs is incredibly important in appreciating and experiencing the art of music. The Purpose of this study is to find out the Contextual Meaning (Context of Situation, Object Context, and Context Of Purpose) on Adele’s someone like you lyrics. Qualitative method were used in this research with descriptive analysis approach so that the research question answered with analytical description. To analyzed the data use theory from Mansoer Patteda and Miles Huberman. From the data and results after analyzing the contextual meaning on Someone Like You lyrics from Adele researcher found there are the Context of the Situation, Object context and Context of Purpose.With 21 Context Situation, 2 Object Context, and 18 Context of Purpose. This research can be used as a reference about Contextual Meaning, more specifically Context Situation, Object Context and Context of Purpose. This Prove Adele Song Someone Like You have a different meaning and contextual depends on each sentence of lyric.